The Urgency of Qawaid Fiqhiyyah and Its Implementation in the Actualization of Islamic Inheritance Law - Mahendra, Bayu Arif; Abdillah, Masykuri; Ramadhan, Taufiq; Hanif, Hamdan Arief (Qanun: Jurnal Hukum Keluarga Islam, 2024)
The human life journey is divided into three important stages: birth, marriage, and death. Each individual leaves assets and responsibilities that must be managed after their death, which are then regulated by inheritance law. Along with rapid social change, there is a mismatch between static Islamic inheritance law and the needs of modern society. Therefore, there is a need to update Islamic inheritance law so that it remains relevant. This update process requires a clear method for discovering and implementing new rules. The principles of fiqh in Islamic inheritance offer a practical approach to finding the necessary legal solutions. With these principles, it is hoped that it can solve contemporary problems and support the reform of Islamic inheritance law. The aim of this research is to examine and evaluate the application of fiqhiyyah rules in Islamic inheritance law. The research method used is qualitative with a content analysis approach. The theory used is the theory of fiqh rules which examines general (kulli) and specific (far'i) rules, especially in the implementation of Islamic inheritance law. The results of this research show that the principles of jurisprudence function as a tool in formulating legal decisions and facilitating the resolution of inheritance cases. These rules of Mawarist fiqhiyyah have an important role in the application of Islamic inheritance law and assist in the maximum actualization of Islamic law through the process of absolute mujtahid ijtihad.